Relationship between vitiligo and Hashimoto's thyroiditis - de Oliveira Andrade, Luis Jesuino; Baptista, Gustavo Magno; Dias, Juliane Santos; Vinhaes Bittencourt, Alcina Maria; França, Larissa Santos (Revista de Ciências Médicas e Biológicas, 2017)
B Background: Vitiligo is a multifactorial acquired depigmenting disorder, characterized by a spontaneous loss of functional melanocytes from the epidermis. Vitiligo and Hashimoto's thyroiditis (HT) often occur in association and seem to be characterized by an autoimmune process. The vitiligo associated with HT suggests genetic homologies between them.Objective: To identify protein sequence homology between melanocyte protein (Pmel) and thyroid peroxidase (TPO), using bioinformatics tools, to propose an initial mechanism which could explain the production of cross-reacting autoantibodies to melanocyte and TPO.Methods: We performed a comparison between Pmel and TPO amino acids (AA) sequences, available on the National Center for Biotechnology Information (NCBI) database by BLAST (Basic Local Alignment Search Tool) in order to find local homology regions between the AA sequences.Results: The homology sequence between the Pmel and TPO ranged from 21.0 % (19 identical residues out of 90 AA in the sequence) to 55.0% (6 identical residues out of 11 AA in the sequence). The identical alignments presented relatively high E values due to presence of short alignment.Conclusion: Bioinformatics data suggest a possible pathological link between Pmel and TPO. Sequence homology between Pmel and TPO may present a molecular mimicry suggesting the possibility of antigen crossover between Pmel and TPO that might represent an immunological basis for vitiligo associated with HT.